2016
DOI: 10.4067/s0719-38902016005000008
|View full text |Cite
|
Sign up to set email alerts
|

ABUNDANCIA Y DEPREDACIÓN DE Ceraeochrysa valida (NEUROPTERA: CHRYSOPIDAE) SOBRE Diaphorina citri (HEMIPTERA: LIVIIDAE) EN COLIMA, MÉXICO

Abstract: RESUMENDiaphorina citri Kuwayama es considerada la plaga más importante de los cítricos por transmitir la bacteria Candidatus Liberibacter spp., causante de la muerte de millones de árboles en el mundo. Para recomendar al depredador Ceraeochrysa valida (Banks) en el control de este insecto se realizaron cuatro ensayos: 1) distribución y presencia de C. valida en huertas de limón en el estado de Colima; 2) máxima capacidad de depredación de C. valida sobre ninfas de D. citri bajo condiciones controladas; 3) tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
2
1
0
1
Order By: Relevance
“…When comparing predation between larval instars, the statistical analysis (α = 0.05) indicated that the third instar had higher voracity than earlier instars (Table 1). This agrees with the results reported by Loera et al (2001), Guarin (2003), Salas and Vela (2003), Velázquez (2004), Pacheco-Rueda et al (2015) and Palomares-Pérez et al (2019). These authors reported that third-instar larvae are more voracious because they need to store the greatest amount of nutrients to be able to carry out the transformation to the adult stage; therefore, they are the ones that carry out most of the biological control activity.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…When comparing predation between larval instars, the statistical analysis (α = 0.05) indicated that the third instar had higher voracity than earlier instars (Table 1). This agrees with the results reported by Loera et al (2001), Guarin (2003), Salas and Vela (2003), Velázquez (2004), Pacheco-Rueda et al (2015) and Palomares-Pérez et al (2019). These authors reported that third-instar larvae are more voracious because they need to store the greatest amount of nutrients to be able to carry out the transformation to the adult stage; therefore, they are the ones that carry out most of the biological control activity.…”
Section: Resultssupporting
confidence: 93%
“…The functional response identified (Type II) is similar with the response identified by Fonseca et al (2000), Auad et al (2001), Castro et al (2016) and Palomares-Pérez et al (2019), who mention that C. externa presented a Type II functional response when feeding on Schizaphis graminum (Rondani), Uroleuconambrosiae (Thomas) (Hemiptera: Aphididae), Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae) and Melanaphis sacchari (Zehntner) (Hemiptera: Aphididae) respectively. Similarly, C. rufilabris presents the same functional response when feeding on Aphis gossypii Glover (Homoptera: Aphididae) and Rhinocapsus vanduzeei Uhle (Hemiptera: Miridae).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Dentro de la familia Chrysopidae se encuentra Ceraeochrysa valida (Banks) (Neuroptera: Chrysopidae), considerado un depredador generalista (Winterton y Makarkin, 2010) y cuya distribución en diferentes estados de la república mexicana (Valencia et al, 2006;CortezMondaca et al, 2011;Córdoba-Urtiz et al, 2014) hacen suponer que tiene gran potencial para ser incluido en programas de control biológico (Palomares-Pérez et al, 2016) (Huang et al, 1984;Bové, 2006) y causante de la muerte de millones de árboles en el mundo (Halbert y Manjunath, 2004;Bové, 2006). Actualmente, el área de Insectos Entomófagos del Centro Nacional de Referencia de Control Biológico (IE-CNRCB) se encuentra desarrollando y validando alternativas que involucran la producción y uso de C. valida como uno de los depredadores con gran potencial para ser utilizado en el control biológico de diversas plagas agrícolas (Tauber et al, 2000).…”
Section: Introductionunclassified